The Role of Family Communication in Insecure Adolescents in the City of Bandung - Dian Yohana Giovani Lumban Siantar; Rita Destiwati (Publikasi Indonesia, 2024)
The phenomenon of insecurity is an issue that is often faced by today's teenagers, characterized by feelings of dissatisfaction with themselves and fear of the surrounding environment. The purpose of this study is to find out the role of family communication in adolescents who experience insecurity in the city of Bandung. This research uses a qualitative approach (Kriyantono, 2012), which investigates social phenomena that occur in humans. The results of the study showed that there was a relationship between feelings of insecurity and decision-making in late adolescence. Adolescents who experience insecurity tend to be hesitant in making their own decisions and often seek validation from others. This study emphasizes the importance of the role of communication in the family, especially democratic communication patterns, which have been proven to help adolescents overcome feelings of insecurity. The three main dimensions that contribute to feelings of insecurity in adolescents are failure or rejection, social anxiety, and the drive for perfectionism. The experience of failure or rejection causes adolescents to feel inferior and incapable in various aspects, which if it happens constantly, can increase feelings of insecurity. It can be concluded that family communication with a good pattern can help adolescents who feel insecure.